Improved lung recruitment and oxygenation during mandatory ventilation with a new expiratory ventilation assistance device: A controlled interventional trial in healthy pigs. Issue 10 (October 2018) - Schmidt, Johannes; Wenzel, Christin; Mahn, Marlene; Spassov, Sashko; Cristina Schmitz, Heidi; Borgmann, Silke; Lin, Ziwei; Haberstroh, Jörg; Meckel, Stephan; Eiden, Sebastian; Wirth, Steffen; Buerkle, Hartmut; et al.
Abstract : BACKGROUND: In contrast to conventional mandatory ventilation, a new ventilation mode, expiratory ventilation assistance (EVA), linearises the expiratory tracheal pressure decline. OBJECTIVE: We hypothesised that due to a recruiting effect, linearised expiration oxygenates better than volume controlled ventilation (VCV). We compared the EVA with VCV mode with regard to gas exchange, ventilation volumes and pressures and lung aeration in a model of peri-operative mandatory ventilation in healthy pigs. DESIGN: Controlled interventional trial. SETTING: Animal operating facility at a university medical centre. ANIMALS: A total of 16 German Landrace hybrid pigs. INTERVENTION: The lungs of anaesthetised pigs were ventilated with the EVA mode ( n =9) or VCV (control, n =7) for 5 h with positive end-expiratory pressure of 5 cmH2 O and tidal volume of 8 ml kg −1 . The respiratory rate was adjusted for a target end-tidal CO2 of 4.7 to 6 kPa. MAIN OUTCOME MEASURES: Tracheal pressure, minute volume and arterial blood gases were recorded repeatedly. Computed thoracic tomography was performed to quantify the percentages of normally and poorly aerated lung tissue. RESULTS: Two animals in the EVA group were excluded due to unstable ventilation ( n =1) or unstable FiO2 delivery ( n =1). Mean tracheal pressure and P a O2 were higher in the EVA group compared with control (mean tracheal pressure: 11.6 ± 0.4 versus 9.0 ± 0.3 cmH2 O, P  < 0.001 and P a O2 : 19.2 ± 0.7 versus 17.5 ± 0.4 kPa, P  = 0.002) with comparable peak inspiratory tracheal pressure (18.3 ± 0.9 versus 18.0 ± 1.2 cmH2 O, P  > 0.99). Minute volume was lower in the EVA group compared with control (5.5 ± 0.2 versus 7.0 ± 1.0 l min −1, P  = 0.02) with normoventilation in both groups ( P a CO2 5.4 ± 0.3 versus 5.5 ± 0.3 kPa, P  > 0.99). In the EVA group, the percentage of normally aerated lung tissue was higher (81.0 ± 3.6 versus 75.8 ± 3.0%, P  = 0.017) and of poorly aerated lung tissue lower (9.5 ± 3.3 versus 15.7 ± 3.5%, P  = 0.002) compared with control. CONCLUSION: EVA ventilation improves lung aeration via elevated mean tracheal pressure and consequently improves arterial oxygenation at unaltered positive end-expiratory pressure (PEEP) and peak inspiratory pressure (PIP). These findings suggest the EVA mode is a new approach for protective lung ventilation. Abstract : Supplemental Digital Content is available in the text